Oxygen isotopes and human mobility in Middle and Late Holocene hunter-gatherer groups from the eastern Pampa-Patagonia transition (Argentina). (10th December 2022) - Flensborg, Gustavo; Tessone, Augusto; Serna, Alejandro; Martínez, Gustavo
Abstract: This work seeks to explore human mobility in the lower course of the Colorado River (Argentina) during the Middle and Late Holocene (ca. 5900-250 years BP) through the analysis of stable oxygen isotopes (δ 18 O) of bone bioapatite. The δ 18 O values are interpreted and compared with those from North Patagonia and Western Pampas to evaluate mobility at a regional scale. Forty-one adult individuals of both sexes from 12 archaeological sites were analyzed. δ 18 Oc values were transformed into drinking water (δ 18 Odw ). The results were compared with the hydrological baseline generated for central-eastern North Patagonia and real rainfall data and predictive rainfall models. ẟ 18 Oc values indicate higher values in individuals corresponding to Middle Holocene (−0.7‰) compared with the Initial Late Holocene (−3.1‰) and Final Late Holocene (−2.3‰) and statistically significant differences between Middle Holocene and Late Holocene. Based on the δ 18 Odw values, 17.1% (7/41) correspond to hydrologic zones defined for central-eastern North Patagonia, and 48.8% to the real and predictive rainfall models. Although differences in δ 18 Odw values are observed between the Middle and Late Holocene, it is not yet possible to propose precise human mobility geographical directions in the study area. Nevertheless, during the Late Holocene, the δ 18 Oc values showed that individuals buried in the study area could have shared some water sources with those from Western Pampas and nearby sectors from Northeastern Patagonia, such as the lower course of the Negro River.